2019
DOI: 10.1055/s-0039-1677724
|View full text |Cite
|
Sign up to set email alerts
|

National Analysis of Risk Factors for Nasal Fractures and Associated Injuries in Trauma

Abstract: Nasal fractures account for up to 58% of facial fractures. However, the literature characterizing associated injuries and risk factors for nasal fractures is sparse and is mostly composed of single-center experiences. This study sought to provide a large descriptive analysis and identify associated injuries and risk factors for nasal fractures in trauma using a national database. A retrospective analysis of the National Trauma Data Bank (NTDB) from 2007 to 2015 was performed. Patients ≥18 years of age with nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Over half of our LEM patients tested positive for ethanol in contrast to only 22% of our HEM patients. Prior studies have recognized ethanol use as a common feature of patients at the time of facial trauma, but the higher prevalence in patients with FFs after LEMs compared to HEMs has not been reported [11,12]. Given the two most common MOIs for the LEM group were assaults and groundlevel falls, our findings further implicate ethanol use as an important factor in these MOIs, and may offer an opportunity for targeted injury-prevention strategies.…”
Section: Discussionmentioning
confidence: 52%
“…Over half of our LEM patients tested positive for ethanol in contrast to only 22% of our HEM patients. Prior studies have recognized ethanol use as a common feature of patients at the time of facial trauma, but the higher prevalence in patients with FFs after LEMs compared to HEMs has not been reported [11,12]. Given the two most common MOIs for the LEM group were assaults and groundlevel falls, our findings further implicate ethanol use as an important factor in these MOIs, and may offer an opportunity for targeted injury-prevention strategies.…”
Section: Discussionmentioning
confidence: 52%
“…The causes of the nasal fractures in this study are shown in Fig. (2). Road Traffic accidents (RTA) were the main cause in 53.8%, whereas the second most frequent cause of fracture was assault from others, reported by 24.7% of the patients.…”
Section: Resultsmentioning
confidence: 74%
“…Being the most prominent central part of the face, the nose is commonly exposed to trauma. Fractures of the nose are the commonest facial fractures forming almost 58% of the fractures of the facial skeleton [1,2]. Causes of nasal bone fractures (NBFs) are variable and differ according to socioeconomic status, geographic areas, cultural and other factors [3].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Studies have suggested an association between maxillofacial fractures and traumatic brain injury (TBI). [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Depending on the severity, TBI may be difficult to detect using current technology, potentially delaying treatment and worsening prognosis for patients. 4 A recent study suggested an association between Le Fort type fractures and more severe TBI.…”
Section: Introductionmentioning
confidence: 99%